Hydrogen production by newly isolated Clostridium species from cow rumen in pure- and co-cultures on a broad range of carbon sources - Vui Thi Hoang; Diem Huong Hoang; Ngoc Duc Pham; Hanh My Tran; Ha Thi Viet Bui; Tien Anh Ngo (AIMS Energy, 2018)
Three novel hydrogen-generating strains, ST1, ST4, and ST5, were isolated from the rumen of cow in Vietnam, and respectively identified as Clostridium beijerinckii ST1, Clostridium bifermentans ST4, and Clostridium butyricum ST5, based on 16S rDNA gene sequence analysis and physiobiochemical characteristics. The dark fermentative hydrogen production of these isolated Clostridium strains was performed and characterized in both pure- and co-cultures from various carbon sources including sucrose, glucose, lactose, xylose, molasses, cassava stumps, and rice distillers wet grains with soluble. The highest hydrogen production was achieved from a co-culture with three Clostridium strains. To optimize the operational conditions of temperature, time, and substrate concentration for the high-level production of hydrogen, response surface methodology in a Box-Behnken design was used. The results revealed a maximum hydrogen production of 1.13 ± 0.015 L H2/L medium by the three-strain co-culture under the following fermentation conditions: 11.63 g/L sucrose, 36.1 °C, in 51.13 h.